Efektivitas Penerapan Metode Pembelajaran Penemuan Terbimbing terhadap Kemampuan Berpikir Kritis Matematika Peserta Didik - Aryawati, Aulia; Mania, Sitti; Yuliany, Nur; Abrar, Andi Ika Prasasti; Halimah, Andi (Al asma : Journal of Islamic Education, 2023)
This study aims to determine students' mathematical critical thinking skills by applying the guided discovery learning method to class VII MTs. Aisyiyah Sungguminasa, Gowa Regency. This type of research is a quasi-experimental research using a research design, namely The Nonequivalent Control Group Design. The population in this study were all students of class VII MTs. Aisyiyah Sungguminasa Gowa Regency totaled 143 people with the sampling technique using simple random sampling technique. The instrument used was an essay test to determine students' critical thinking skills in mathematics. The analysis technique used is descriptive and inferential statistical analysis. Based on the results of the descriptive analysis showed that the average critical thinking ability of students using the guided discovery learning method reached the very high category, while those without using the guided discovery learning method reached the moderate category. Furthermore, the results of the inferential analysis using the t test show that there is a significant difference between the mathematical critical thinking skills of students who apply the guided discovery learning method and those who do not apply the guided discovery learning method.